A distributed software architecture based on reactive microservices for the Smart Building context - Freire, Gustavo; Paucar, Herminio; Estrella, Júlio (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Companion Proceedings of the 12th Latin-American Symposium on Dependable Computing, 2023)
Given the increasing urbanization of the world’s population, Smart Building (SB) technologies can improve living conditions and sustainability. This article investigates Distributed Software Architecture (DSA) use in SBs, guided by the Reactive Manifesto (RM) principles and Cloud Patterns. The proposed DSA, offers scalability, lower latency, distributed processing, flexibility, and enhanced security, aims for adaptability, cost-effectiveness, and high performance. The research follows a two-phase development process involving scenario simulations and deployment at the Laboratory of Distributed Systems and Concurrent Programming (LaSDPC) at ICMC-USP. The paper proposes a cloud-based system with low operational costs that caters to different use cases. By delivering a design in line with the latest distributed software engineering best practices for IoT applications, we aim to contribute to this field. The architecture will be tested in real-world settings at LaSDPC, with potential applications in smart homes and Industry 4.0.